2017
DOI: 10.1155/2017/4078346
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Approaches and Role of ncRNAs in Cardiovascular Disorders and Insulin Resistance

Abstract: Diseases resulting from alterations in gene expressions through mutations in the genes or through changes in the gene expression regulation could be identified through the analysis of RNA expressions. ncRNAs play a significant role in regulation of the gene expression by controlling the expression levels of the coding RNAs and other cellular processes. Discoveries have shown that the human genome is encoded with sequences responsible for the transcription of thousands of ncRNAs. Even though the studies conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
(83 reference statements)
0
9
0
Order By: Relevance
“…Normally, the tumor would remain concealed in the early stages, whereas it could progress fast; therefore, the disease of most patients is found during the advanced stage [4]. Recent findings have uncovered that approximately 98% of human genome transcripts are ncRNAs, which have little or even no protein-coding capability [5]. LncRNAs, which are no less than 200 nt in length, are dominant in the ncRNA family [6].…”
Section: Introductionmentioning
confidence: 99%
“…Normally, the tumor would remain concealed in the early stages, whereas it could progress fast; therefore, the disease of most patients is found during the advanced stage [4]. Recent findings have uncovered that approximately 98% of human genome transcripts are ncRNAs, which have little or even no protein-coding capability [5]. LncRNAs, which are no less than 200 nt in length, are dominant in the ncRNA family [6].…”
Section: Introductionmentioning
confidence: 99%
“…Recent findings have uncovered the transcription of long non‐coding RNAs (lncRNAs) from human genome with the development of high‐throughput sequencing 7‐9 . lncRNAs, which are more than 200 nucleotides long, have no or limited protein‐coding capacity 10 .…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA accounts for 68% of ncRNAs (Iyer et al, 2015), but they were considered ''junk RNA'' in the genome because they could not encode proteins (Zhang et al, 2019). However, recent studies have shown that lncRNA exert critical roles in regulating biological processes through comprehensive mechanisms, including genetic imprinting, immune response, tumorigenesis, cellular development and metabolism (Liyanage & Ganegoda, 2017). LncRNAs are also involved in the regulation of glucose and lipid metabolism in the liver, and their abnormal expression may be involved in the development of type 2 diabetes mellitus (T2DM) (Eslam, Valenti & Romeo, 2018).…”
Section: Introductionmentioning
confidence: 99%